Problematika Ta’arud Al-Adillah Dalam Menyelesaikan Masalah Hukum - Arham, Ghina Ghefira Fadhia; Rahmat, Anugrah Safitri; k, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Qur'an is the first and main authority in the Islamic religion, in viewing a law or resolving a problem faced by humans on this earth. Fiqh proposals present various ways with various aspects to capture the legal messages presented by the Koran and Sunnah, as well as solutions that can be implemented if there is a contradiction between several equivalent propositions or between other propositions. Legally, the research method used is normative juridical. In this type of legal research, law is often conceptualized as what is written in statutory regulations (law in books). Ta'arud al-Adillah is a term in the science of ulus fiqh which refers to the conflict or contradiction between the postulates of sharia law. The essence lies in how the ulama and mujtahid resolve the conflict to reach the right legal conclusion. The Ta'arud al-Adillah method of interpretation, which refers to the conflict between legal postulates in the science of ulus fiqh. The scholars use principles such as tarjih (preference), talfiq (combination), or takhsis (special explanation) to complete ta'arudh al-adillah. The al-jam'u method on this problem is more appropriate than using the al-naskh method. One way to apply the al-jam'u method is by discussing the propositions of 'aam. The implementation of Ta'arud al-Adillah in Islamic legal practice involves systematic steps and careful principles. First of all, fiqh experts must recognize the existence of conflicts between various legal propositions that are relevant in a particular context.